Apontamentos sobre a (in)existência de elementos religiosos na tradição inventada cubana: subsídios para reflexões sobre uma eventual dimensão religiosa pública = Notes on the (in)existence of religious elements in the Cuban invented tradition : subsidies for reflections on an eventual public religious dimension - Horacio, Heiberle Hirsgberg (Ciencias sociales y religión, 2016)
This article examines the relation between state and religion in Cuba, analyzes the symbolic elements, the narratives and discursive structures that composes the process of invention of Cuban tradition, and also if this process is permeated by traditional religious traces stablished. Thus, this article performs the examination of the relation between state and religion in Cuba trough a kind of bibliographic review and develops analyzes of the statements of Cuban press, in specific the newspaper “juventud Rebelde” and also analyzes a public-politic ethnographic ritual “dia de la rebeldia nacional”; july 26 (the Day of the National Rebellion). However, this article is not trying to defend the existence of a laic religiosity in Cuba (in terms of a political religion) neither the existence of a public religious dimension, but enable some reflections that articulate those notions and the Cuban political experience.